The Role of The Principal as a Supervisor in the Implementation of the Independent Curriculum in the Al-Hafizh Banyuasin Playgroups - Apriyanti, Eni; Ahmad, Syarwani; Kesumawati, Nila (Raudhah Publisher, 2024)
Supervision is a monitoring, training and evaluation activity carried out by a supervisor or head of school to improve and improve the quality of learning and school activities. The research uses descriptive qualitative approaches with case study methods and data collection techniques such as interviews, documentation and observations. The results of the study are the supervised approaches used by the head of the Al-Hafizh group to learn, namely Teacher Centered-Approach and Student Centered and Teacher-centered. Some of the approaches that the leader of the group uses in supervising today are Direct Approach, Non-Direct Approaching and collaborative approaches. Al-Hafizh joint teachers of the learning group work together to pursue a continuous improvement in the learning management and school administration system that includes training and supervision on the implementation of learning by teachers. Such as the ability of teachers to conduct learning planning, use of learning media, mastery of social personal learning materials and classroom management. As well as realizing a sense of family through intensive communication or other persuasion approaches, so that the Al-Hafizh playgroup becomes a school that seeks to develop its qualities according to the conditions of the institution and the demands of the times.